Penerapan Studi Hadis Tematik tentang Alam dan Ilmu Pengetahuan - Muzibul Khoir; Muhammad Alif (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
The thematic study of hadiths (maudhu'i) concerning nature and science is a significant approach to understanding Islam's contribution to environmental preservation and the development of modern scientific knowledge. This research aims to examine the hadiths of Prophet Muhammad ﷺ related to environmental conservation, natural phenomena, and their integration with contemporary scientific findings. The method used is qualitative research with a library research approach, where primary data were obtained from authentic hadith collections such as Sahih Bukhari and Sahih Muslim, and analyzed thematically. The results of the discussion indicate that the concept of environmental conservation in Islam is reflected in the principle of hima, as well as hadiths that encourage tree planting and the protection of living beings. Hadiths about natural phenomena such as the sea, rain, and wind contain both spiritual and educational messages that support ecological awareness. Furthermore, the integration of hadith with modern science, such as embryology, demonstrates that Islam supports scientific exploration as a form of worship and a means of understanding the greatness of Allah’s creation. In conclusion, thematic hadith studies not only enrich the understanding of the relationship between religion and science among Muslims but also provide an ethical foundation for building a faithful, knowledgeable, and environmentally responsible society that contributes to scientific advancement.